The Effect of the Parental Treatment Style of the Firm Mother on Social Adjustment in University Life Among Students of Sultan Qaboos University in the Sultanate of Oman - Alsharji, Farida Said; Mansour, Norwati (Journal of Educational and Psychological Sciences, 2025)
The current study is aimed to reveal the effect of the firm mother’s parental treatment style on social adjustment in university life amongst the students of Sultan Qaboos University in the Sultanate of Oman. The study followed the descriptive correlational approach. The researcher used the translated into Arabic Buri’s Parental Treatment Styles Scale (Buri, 1991); standardized to the Omani environment by Al-Dhafri et al. (2011) and developed by Al-Kharousi et al. (2011). The researcher used also the University Life Adjustment Scale; prepared by Hajjo (2015) and adapted to the Omani environment by Al-Shandoudiya (2020). The study was applied on a sample of (793) male and female students who were selected by the simple random sample (SRS) method. The study’s results showed a significant, positive, and direct effect of the firm mother’s parental treatment style on the social adjustment in university life amongst the students of Sultan Qaboos University in the Sultanate of Oman. The beta coefficient (0.238) indicated that the students who were exposed to firm parenting treatment showed higher levels of social adjustment at university. However, the results showed no statistically significant differences between males and females in the parental treatment style of the strict mother on social adjustment in university life amongst university students indicating that there are no significant differences attributed to the gender variable; males and females are exposed to the same strict parental upbringing, and they enjoy the same degree of social adjustment. The study recommended further studies that focus on the impact of other parental styles, such as leniency or control, on the social and psychological adjustment of university students.